Thermoelectric conversion element, method for manufacturing thermoelectric conversion element, bonding material, thermoelectric conversion module, thermoelectric conversion system, and power generation method

By configuring a bonding layer with Fe and Ni content in the thermoelectric conversion element, the problem of rising resistance caused by Mg oxidation or sublimation in high-temperature air is solved, and the stability and long life of the thermoelectric conversion performance are achieved.

CN119769214AInactive Publication Date: 2025-04-04PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380061654.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-29
Filing Date
2023-08-01
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In a high-temperature air environment, the thermoelectric conversion element containing Mg and Sb/Bi thermoelectric conversion materials is prone to increase resistance due to the oxidation or sublimation of Mg, thereby reducing the thermoelectric conversion performance.

Method used

A bonding layer containing Fe and Ni is arranged between the metal layer and the thermoelectric conversion material layer, and the ratio of the Mg content to the Sb and Bi content of the bonding layer satisfies the condition of 2.5≤α/β≤6.5 to suppress the loss of Mg and the increase in resistance.

Benefits of technology

It effectively suppresses the rise in the resistance of the thermoelectric conversion element in high-temperature air, stabilizes the thermoelectric conversion performance, and extends the service life of the component.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119769214A_ABST
    Figure CN119769214A_ABST
Patent Text Reader

Abstract

Provided is a thermoelectric conversion element which is advantageous from the perspective of suppressing an increase in resistance in high-temperature air. This thermoelectric conversion element (10) is provided with a first metal layer (15) and a thermoelectric conversion section (11a). The thermoelectric conversion part (11a) contains Mg and at least one selected from the group consisting of Sb and Bi. The thermoelectric conversion part (11a) is provided with a thermoelectric conversion layer (11) and a first bonding layer (14). The first bonding layer (14) contains at least one selected from the group consisting of Fe and Ni. The first bonding layer (14) satisfies the condition 2.5 < = alpha / beta < = 6.5. In this condition, alpha is the content of Mg in the first bonding layer (14) on the basis of the number of atoms, and beta is the sum of the content of Sb and Bi in the first bonding layer (14) on the basis of the number of atoms.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a thermoelectric conversion element, a bonding material, a thermoelectric conversion module, a thermoelectric conversion system, a power generation method, and a method for manufacturing a thermoelectric conversion element. Background Art

[0002] Conventionally, thermoelectric conversion materials containing Mg and at least one selected from Sb and Bi are known.

[0003] For example, Patent Document 1 records that Mg 3+m A a B b D 2-e E e A thermoelectric conversion material represented by . In the thermoelectric conversion material, D is at least one selected from Sb and Bi.

[0004] Non-patent document 1 describes a predetermined n-type Mg 3+δ (Sb, Bi) thermoelectric conversion performance. For example, 3.2 Sb 1.5 Bi 0.49 Te 0.01 The polycrystalline sintered body of the composition exhibits a ZT of 1.51±0.06 at 716K.

[0005] Non-patent document 2 describes n-type Mg 3.1 Co 0.1 Sb 1.5 Bi 0.49 Te 0.01 The sample is produced by placing powder of a thermoelectric conversion material on a graphite mold in a state of being sandwiched by iron powder and hot-pressing the powder.

[0006] Non-patent document 3 describes n-type Mg 3.2 Sb 1.5 Bi 0.49 Te 0.01 Bonding with stainless steel (SUS304).

[0007] Patent Document 2 describes a thermoelectric conversion element in which a pair of electrode layers made of a metal material are formed on both sides of a thermoelectric conversion layer made of magnesium silicide. In the thermoelectric conversion element, a buffer layer made of a mixture of magnesium silicide and a metal material is formed between the thermoelectric conversion layer and the electrode layer. The metal material is a nickel-based material.

[0008] Prior Art Literature

[0009] Patent Document 1: Japanese Patent No. 6127281

[0010] Patent Document 2: Japanese Patent Application Publication No. 2009-260173

[0011] Non-patent document 1: Tamaki et al., Advanced Materials 28, 10182-10187 (2016)

[0012] Non-patent document 2: Zhu et al., Journal of Power Sources 414, 393-400 (2019)

[0013] Non-patent document 3: Yin et al., Acta Materialia 198, 25-34 (2020) Summary of the invention

[0014] Problems to be solved by the invention

[0015] The present disclosure provides a thermoelectric conversion element which is advantageous from the viewpoint of suppressing an increase in electrical resistance in high-temperature air.

[0016] Means for solving problems

[0017] The thermoelectric conversion element disclosed in the present invention comprises a first metal layer and a thermoelectric conversion unit.

[0018] The thermoelectric conversion unit contains Mg and at least one selected from Sb and Bi,

[0019] The thermoelectric conversion unit includes a thermoelectric conversion layer and a first bonding layer.

[0020] The first bonding layer is arranged between the first metal layer and the thermoelectric conversion layer in the thickness direction of the thermoelectric conversion layer.

[0021] The first bonding layer contains at least one selected from Fe and Ni,

[0022] The first bonding layer satisfies a first condition represented by 2.5≤α / β≤6.5,

[0023] In the first condition, α is the content rate of Mg in the first bonding layer based on the number of atoms, and β is the sum of the content rates of Sb and Bi in the first bonding layer based on the number of atoms.

[0024] Effects of the Invention

[0025] According to the present disclosure, it is possible to provide a thermoelectric conversion element which is advantageous from the viewpoint of suppressing an increase in electrical resistance in high-temperature air. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1This is a cross-sectional view schematically showing the thermoelectric conversion element according to Embodiment 1.

[0027] Figure 2 This is a flowchart showing the method for manufacturing the thermoelectric conversion element according to the first embodiment.

[0028] Figure 3 This is a cross-sectional view schematically showing an example of a thermoelectric conversion element according to Embodiment 2.

[0029] Figure 4 This is a cross-sectional view schematically showing another example of the thermoelectric conversion element according to the second embodiment.

[0030] Figure 5 This is a perspective view showing a thermoelectric conversion module according to Embodiment 3.

[0031] Figure 6 It is a side view showing the thermoelectric conversion system of Embodiment 4.

[0032] Figure 7 This is a scanning electron microscope image of a cross section of the junction portion of the thermoelectric conversion element of Example 1.

[0033] Figure 8 This is a scanning electron microscope image of a cross section of a junction portion of the thermoelectric conversion element of Example 6. DETAILED DESCRIPTION

[0034] (Insights that form the basis of this disclosure)

[0035] Thermoelectric conversion technology for generating electricity by converting thermal energy into electrical energy through solid elements is widely known. It can be considered to connect n-type thermoelectric conversion elements and p-type thermoelectric conversion elements in series and in parallel on a substrate to form a flat thermoelectric conversion module. Power generation is performed by applying a temperature difference to such a thermoelectric conversion module. In order to achieve good electrical connection in the thermoelectric conversion module, it can be considered to use a thermoelectric conversion element in which metal plating is applied to the thermoelectric conversion material, or a thermoelectric conversion element in which metal powder or metal plate is joined to the thermoelectric conversion material by sintering or other methods. When generating electricity through the thermoelectric conversion element, the thermoelectric conversion element is sometimes placed in an environment of high temperature air (for example, 400°C air) for a long time. Even in such a case, it is important to suppress the increase of resistance in the thermoelectric conversion element.

[0036] Patent Document 1 records that Mg 3+m A a B b D 2-e E e The invention discloses a thermoelectric conversion material, but does not describe the structure of a thermoelectric conversion element including the thermoelectric conversion material.

[0037] Non-patent document 1 describes a method for improving n-type Mg 3+δ The thermoelectric conversion performance of the thermoelectric conversion material of (Sb, Bi) requires the presence of excess Mg relative to the stoichiometric ratio. On the other hand, according to the research of the present inventors, Mg is easily oxidized and has a high vapor pressure. Therefore, in a high-temperature air environment, due to the oxidation or sublimation of Mg, the Mg in the thermoelectric conversion material containing Mg and at least one selected from Sb and Bi is easily lost. As a result, when such a thermoelectric conversion material is placed in a high-temperature air environment for a long time, there is a problem that the resistance of the thermoelectric conversion element increases and the thermoelectric conversion performance is easily reduced. The present inventors focused on this issue.

[0038] Therefore, the present inventors have conducted intensive studies on a configuration in which the resistance of a thermoelectric conversion element including a thermoelectric conversion material containing Mg and at least one selected from Sb and Bi is unlikely to increase in high-temperature air.

[0039] Non-patent document 2 describes a sample produced by placing powder of a thermoelectric conversion material on a graphite mold in a state where it is sandwiched by iron powder and hot pressing the powder. 3.2 Sb 1.5 Bi 0.49 Te 0.01 Joining with stainless steel (SUS304) According to the reproduction experiment of the samples described in Non-Patent Documents 2 and 3 conducted by the present inventors, it was found that there was a deviation in the initial characteristics of the reproduced samples and the resistance of the samples increased in high temperature air.

[0040] In the thermoelectric conversion element described in Patent Document 2, a buffer layer composed of a mixture of magnesium silicide and a metal material is formed between a thermoelectric conversion layer composed of magnesium silicide and an electrode layer. However, in this thermoelectric conversion element, there is no excess Mg relative to the stoichiometric ratio, and Patent Document 2 does not provide insights for solving the above-mentioned problems related to the thermoelectric conversion element.

[0041] Therefore, the inventors have repeatedly conducted a large number of trial and error, and have newly discovered that by configuring a predetermined bonding layer between the metal layer and the layer containing the thermoelectric conversion material, the resistance of the thermoelectric conversion element is not easily increased in high-temperature air. Based on this new insight, the inventors have completed the thermoelectric conversion element disclosed in the present invention.

[0042] (Embodiments of the present disclosure)

[0043] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.

[0044] (Implementation Method 1)

[0045] Figure 12 is a cross-sectional view schematically showing a thermoelectric conversion element according to Embodiment 1. Figure 1 As shown, the thermoelectric conversion element 10 includes a first metal layer 15 and a thermoelectric conversion portion 11a. The thermoelectric conversion portion 11a contains Mg and at least one selected from Sb and Bi. The thermoelectric conversion portion 11a includes a thermoelectric conversion layer 11 and a first bonding layer 14. The first bonding layer 14 contains at least one selected from Fe and Ni. The first bonding layer 14 satisfies the condition of 2.5≤α / β≤6.5. Under this condition, α is the content rate of Mg in the first bonding layer 14 based on the number of atoms, and β is the sum of the content rates of Sb and Bi in the first bonding layer 14 based on the number of atoms. By configuring the first bonding layer 14 in this way, even if the thermoelectric conversion element 10 is placed in an environment of high-temperature air (for example, air at 400°C), it is easy to suppress the increase in the resistance of the thermoelectric conversion element 10. It is considered that even if the thermoelectric conversion element 10 is placed in an environment of high-temperature air, Mg is difficult to be lost from the thermoelectric conversion material contained in the thermoelectric conversion layer 11 through the first bonding layer 14.

[0046] The first bonding layer 14 may satisfy the condition of α / β≥2.6, the condition of α / β≥2.8, or the condition of α / β≥3.0.

[0047] like Figure 1 As shown, the first bonding layer 14 is arranged between the thermoelectric conversion layer 11 and the first metal layer 15, for example, in the thickness direction of the first bonding layer 14. One main surface (first main surface) of the first bonding layer 14 is in contact with the thermoelectric conversion layer 11, and the other main surface (second main surface) of the first bonding layer 14 is in contact with the first metal layer 15.

[0048] As long as the condition of 2.5≤α / β≤6.5 is satisfied, α is not limited to a specific value. For example, the condition of 18%≤α≤32% may be satisfied, the condition of 18%≤α≤30% may be satisfied, or the condition of 19%≤α≤30% may be satisfied.

[0049] As long as the condition of 2.5≤α / β≤6.5 is satisfied, β is not limited to a specific value. For example, the condition of 3%≤β≤15% may be satisfied, the condition of 4%≤β≤12% may be satisfied, or the condition of 4%≤β≤10% may be satisfied.

[0050] The structure of the first bonding layer 14 is not limited to a specific structure as long as it contains at least one selected from Fe and Ni and satisfies the condition of 2.5≤α / β≤6.5. Figure 1As shown, the first bonding layer 14 includes, for example, particles 14a and a phase 14b that forms a solid phase different from the particles 14a. The particles 14a contain at least one selected from Fe and Ni. The phase 14b exists between the particles 14a. In addition, the phase 14b contains Mg. According to such a structure, even if the thermoelectric conversion element 10 is placed in an environment of high-temperature air, it is easier to suppress the increase in the resistance of the thermoelectric conversion element 10.

[0051] The phase 14b may be a continuous phase or a dispersed phase. The melting point of the phase 14b is, for example, lower than the melting point of the particles 14a.

[0052] The sum γ of the content of Fe and Ni in the first bonding layer 14 based on the number of atoms is not limited to a specific value. The first bonding layer 14 satisfies the condition of γ ≥ 65%, for example. According to such a structure, the resistance of the thermoelectric conversion element 10 is not easy to increase. In addition, the bonding strength between the thermoelectric conversion layer 11 and the first metal layer 15 is easy to increase.

[0053] The first bonding layer 14 may satisfy the condition of γ≥66%, the condition of γ≥67%, or the condition of γ≥68%. For example, the first bonding layer 14 satisfies the condition of γ≤80%.

[0054] In the first bonding layer 14, the ratio α / γ is not limited to a specific value. The first bonding layer 14 satisfies the condition of 0.002<α / γ<0.6, for example. According to such a structure, even if the thermoelectric conversion element 10 is placed in an environment of high temperature air, it is easier to suppress the increase in resistance of the thermoelectric conversion element 10. In addition, the bonding strength between the thermoelectric conversion layer 11 and the first metal layer 15 is likely to be increased.

[0055] In the first bonding layer 14 , α / γ may be included in a range determined by a pair of values ​​selected from 0.005, 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, and 0.5.

[0056] like Figure 1 As shown, for example, the thermoelectric conversion layer 11 is disposed in the thickness direction between the first composite metal layer 12 and the second composite metal layer 13. The first composite metal layer 12 and the second composite metal layer 13 include a first bonding layer 14 and a first metal layer 15, respectively.

[0057] The three-dimensional shape of the thermoelectric conversion element 10 is not limited to a specific shape. The thermoelectric conversion element 10 may be a rectangular parallelepiped. In this case, Figure 1 The cross section of the thermoelectric conversion element 10 perpendicular to the paper plane is rectangular or square. The thermoelectric conversion element 10 may also be cylindrical. In this case, Figure 1 The cross section of the thermoelectric conversion element 10 perpendicular to the paper plane is a circle. The thermoelectric conversion element 10 may also be Figure 1The cross section of the thermoelectric conversion element 10 perpendicular to the paper plane has an irregular shape.

[0058] The thickness of each layer in the thermoelectric conversion element 10 is not limited to a specific value. The thickness of the thermoelectric conversion layer 11 is, for example, greater than 0.5 mm and less than 10 mm. The thickness of the first bonding layer 14 is, for example, greater than 0.01 mm and less than 0.2 mm. The thickness of the first metal layer 15 is, for example, greater than 0.05 mm and less than 1 mm. From the perspective of the manufacturing cost of the thermoelectric conversion element 10 and the operability in the manufacture of the thermoelectric conversion element 10, it is advantageous for the thickness of each layer to be within such a range.

[0059] Figure 1 The cross-sectional views shown are schematic. The multiple interfaces formed by the various parts forming the layered structure may be parallel to each other or may not be parallel to each other. The interfaces may have concave and convex shapes. The cross-sectional shape may be rectangular, and the side of the cross-sectional shape may have concave and convex shapes or bends. A pair of adjacent sides in the cross-sectional shape may cross at right angles, or may cross in a manner that forms an angle less than 90° or an angle greater than 90° and less than 180°.

[0060] The thermoelectric conversion material contained in the thermoelectric conversion layer 11 is not limited to a specific material as long as it contains Mg and at least one selected from Sb and Bi. The thermoelectric conversion layer 11 includes, for example, a La2O3 type crystal structure and Mg 3+m A a D 2- e E e An n-type thermoelectric conversion material of a composition. In the composition, element A is at least one element selected from La, Y, Yb, Mn and Zn. Element D is at least one element selected from Sb and Bi. Element E is at least one element selected from Te and Se. The value of m is greater than -0.1 and less than 0.4. The value of a is greater than 0 and less than 0.1. The value of e is greater than 0.001 and less than 0.06.

[0061] The thermoelectric conversion layer 11 may contain the same element as the element contained in the first bonding layer 14. For example, the same element as the element contained in the first bonding layer 14 derived from the raw material of the first bonding layer 14 may be contained in the thermoelectric conversion layer 11.

[0062] Particle 14a may contain only one of Fe and Ni, or may contain both Fe and Ni. Particle 14a may contain single substance Fe, or may contain single substance Ni. Particle 14a may include an alloy containing at least one selected from Fe and Ni. For example, particle 14a may include an iron-based alloy such as stainless steel, or may include a nickel-based alloy such as Inconel and Hastelloy. Inconel and Hastelloy are registered trademarks. Particle 14a may contain metals other than Fe and Ni. Particle 14a may contain metals such as Cr and Mo, for example.

[0063] Particle 14a may contain the same element as that contained in thermoelectric conversion layer 11 or phase 14b. For example, the same element as that contained in thermoelectric conversion layer 11 or phase 14b derived from the raw material of thermoelectric conversion layer 11 or the raw material of phase 14b may be contained in particle 14a.

[0064] The average particle size q of the particles 14a is not limited to a specific value. The average particle size q satisfies, for example, the condition of 0.5 μm ≤ q ≤ 100 μm. In this case, the bonding strength between the thermoelectric conversion layer 11 and the first metal layer 15 is likely to be high. The average particle size q is, for example, the median particle size d50 in the volume-based particle size distribution obtained by laser diffraction particle size distribution measurement.

[0065] Phase 14b may contain the same element as that contained in thermoelectric conversion layer 11 or particle 14a. For example, the same element as that contained in thermoelectric conversion layer 11 or particle 14a derived from the raw material of thermoelectric conversion layer 11 or the raw material of particle 14a may be contained in phase 14b.

[0066] The metal contained in the first metal layer 15 is not limited to a specific metal. The first metal layer 15 contains, for example, at least one selected from Fe, Ni, Cu, and Ag. In this case, the resistance of the thermoelectric conversion element 10 is easily reduced.

[0067] The first metal layer 15 may contain Fe, Ni, Cu, or Ag. The first metal layer 15 may include an alloy. Examples of the alloy include stainless steel, Inconel, and Hastelloy. The first metal layer 15 may contain oxygen-free copper.

[0068] An example of a method for manufacturing the thermoelectric conversion element 10 will be described. Figure 2: is a flowchart showing a method for manufacturing a thermoelectric conversion element of embodiment 1. The manufacturing method includes, for example, heating a metal plate, a powder, and a bonding material in a predetermined state, sintering the powder, and bonding the metal plate to the sintered body of the powder. The predetermined state refers to a state in which a bonding material is arranged between the metal plate and the powder in the thickness direction of the metal plate. The bonding material contains Mg and at least one selected from Fe and Ni. The powder contains Mg and at least one selected from Sb and Bi.

[0069] like Figure 2 As shown, in step S1, powder is prepared. The powder is prepared by, for example, weighing a predetermined amount of raw materials according to a known powder production method using an arc melting method and a ball mill. The powder can be prepared by referring to the methods described in non-patent documents 1 to 3. The powder is, for example, the powder of the above-mentioned thermoelectric conversion material.

[0070] In step S2, a bonding material is prepared. As described above, the bonding material contains Mg and at least one selected from Fe and Ni, and can bond the thermoelectric conversion material to the metal member.

[0071] The bonding material is, for example, a paste-like composition. The bonding material is prepared by mixing, for example, a high-melting-point metal-containing powder as a raw material of the particles 14a, a low-melting-point Mg-containing powder as a raw material of the phase 14b, an organic binder, and an organic solvent. The high-melting-point metal-containing powder contains, for example, at least one selected from Fe and Ni. The metal powder may be a powder of simple Fe, a powder of simple Ni, or a powder of an alloy containing at least one selected from Fe and Ni. Examples of alloys include stainless steel, Inconel, and Hastelloy. The low-melting-point Mg-containing powder may be a powder of simple Mg, or a powder of an alloy containing Mg. Examples of alloys include alloys of Mg and Cu.

[0072] The average particle size p of the particles contained in the metal-containing powder is not limited to a specific value. The average particle size p satisfies the condition of 0.5 μm ≤ p ≤ 100 μm, for example. As a result, it is easy to improve the bonding strength between the thermoelectric conversion material and the metal component. The average particle size p is, for example, the median particle size d50 in the volume-based particle size distribution obtained by laser diffraction particle size distribution measurement.

[0073] The average particle size p may satisfy the condition of 1 μm ≤ p ≤ 50 μm, the condition of 2 μm ≤ p ≤ 50 μm, or the condition of 5 μm ≤ p ≤ 30 μm.

[0074] The ratio of the content of the high melting point metal-containing powder in the bonding material to the content of the Mg-containing powder in the bonding material is, for example, 97 / 3 or more and 99.5 / 0.5 or less on a mass basis. Thus, even if the manufactured thermoelectric conversion element 10 is placed in an environment of high temperature air, it is easier to suppress the increase in the resistance of the thermoelectric conversion element 10. In addition, in the manufacture of the thermoelectric conversion element 10, it is possible to prevent the molten Mg from leaking from the Mg-containing powder to the outside and the diffusion of Mg to the thermoelectric conversion material from becoming significant. As a result, the thermoelectric conversion element 10 can be easily and stably manufactured.

[0075] The organic binder contained in the bonding material is not limited to a specific organic binder. The organic binder has the property that it evaporates or decomposes during the manufacture of the thermoelectric conversion element 10 and is difficult to remain in the thermoelectric conversion element 10. The organic binder is, for example, a butyl rubber-based resin or an acrylic resin. The organic solvent dissolves or disperses the organic binder. The organic solvent is, for example, a cycloalkane solvent or toluene.

[0076] In the preparation of the bonding material, before adding the metal-containing powder, a bonding solution in which the organic binder is preliminarily dissolved or dispersed in an organic solvent can be prepared. The concentration of the organic binder in the bonding solution is, for example, 1% by mass or more and 15% by mass or less. In this case, the bonding material easily has a viscosity suitable for coating. The ratio of the mass of the metal-containing powder in the bonding material to the mass of the bonding solution is, for example, 3 / 2 to 9. In this case, the bonding material easily has a viscosity suitable for coating.

[0077] In step S3, a bonding material is applied to the metal plate and dried. The method of applying the bonding material to the metal plate is not limited to a specific method. The method includes, for example, a scraper method. During the drying of the bonding material, the organic solvent is evaporated to obtain a dry coating. The drying of the bonding material can be performed using a heating plate or an oven. In this way, a precursor of the first composite metal layer 12 and the second composite metal layer 13 is obtained. The metal plate is, for example, a circular plate.

[0078] In step S4, according to Figure 1 In the configuration shown, the powder prepared in step S1 and the precursors of the first composite metal layer 12 and the second composite metal layer 13 prepared in step S3 are filled into a cylindrical carbon sintering mold. In other words, the powder and the precursors of the first composite metal layer 12 and the second composite metal layer 13 are arranged in such a manner that a bonding material is arranged between the metal plate and the powder in the thickness direction of the metal plate. The metal plate has, for example, a diameter that is less than the inner diameter of the sintering mold. Then, the sintering mold is clamped by a punch in the thickness direction of the metal plate.

[0079] In step S5, the sintering of the powder and the joining of the sintered body of the powder with the metal plate are performed under the state that the punch is pressed to the inside of the sintering mold. Thus, a laminate formed by the joining of the sintered body of the powder with the metal plate is obtained. The sintering of the powder can be performed according to the method of the electric heating method such as the discharge plasma sintering method, or it can be performed according to the hot pressing method accompanied by heating with an electric heater or high-frequency heating. The sintering of the powder is performed, for example, in an argon atmosphere or vacuum with a low oxygen partial pressure. Thus, the thermoelectric conversion material contained in the powder is not easily oxidized. The sintering of the powder is preferably performed in an argon atmosphere. In this case, Mg is not easy to evaporate.

[0080] The sintering temperature of the powder is, for example, above the melting point of Mg, which is 650° C. or above. When the first metal layer 15 contains at least one selected from Fe and Ni, the sintering temperature of the powder can be adjusted to about 900° C. On the other hand, when the first metal layer 15 contains Cu or Ag, the sintering temperature of the powder can be adjusted to 720° C. or below. This can prevent the metal component contained in the first metal layer 15 from being dissolved in Mg and melting.

[0081] In step S6, the laminate obtained in step S5 is taken out from the sintering mold and cut to obtain a rectangular parallelepiped thermoelectric conversion element 10. The method of cutting the laminate is not limited to a specific method. For example, the laminate can be cut using a diamond cutter or a wire saw.

[0082] (Implementation Method 2)

[0083] Figure 3 1 is a cross-sectional view schematically showing an example of a thermoelectric conversion element of Embodiment 2. The thermoelectric conversion element of Embodiment 2 is configured in the same manner as the thermoelectric conversion element of Embodiment 1 except for the parts specifically described. The components of the thermoelectric conversion element of Embodiment 2 that are the same as or correspond to the components of the thermoelectric conversion element of Embodiment 1 are marked with the same symbols, and their detailed description is omitted. The description of the thermoelectric conversion element of Embodiment 1 is also applicable to Embodiment 2 as long as there is no technical contradiction.

[0084] like Figure 3As shown, the thermoelectric conversion element 30 includes a second metal layer 35 in addition to the first metal layer 15 and the thermoelectric conversion part 11a. The second metal layer 35 contains at least one selected from Cu and Ag. The first metal layer 15 is arranged between the second metal layer 35 and the thermoelectric conversion part 11a in the thickness direction of the first metal layer 15. In addition, the first metal layer 15 contains at least one selected from Fe and Ni. According to such a configuration, when a thermoelectric conversion module is manufactured using a plurality of thermoelectric conversion elements 30, the operation for electrically connecting the thermoelectric conversion element 30 and other thermoelectric conversion elements adjacent to the thermoelectric conversion element 30 is easy to perform. In addition, even if the second metal layer 35 is arranged at the end of the thermoelectric conversion element 30 in the thickness direction of the first metal layer 15, the temperature for joining the first metal layer 15 and the second metal layer 35 to the thermoelectric conversion part 11a can be increased to about 900°C.

[0085] In the thermoelectric conversion element 30 , the first metal layer 15 may contain a single substance of Fe, a single substance of Ni, or an alloy containing at least one selected from Fe and Ni. Examples of the alloy include stainless steel, Inconel, and Hastelloy.

[0086] In the thermoelectric conversion element 30 , the second metal layer 35 includes, for example, Cu or Ag.

[0087] like Figure 3 As shown, the thermoelectric conversion element 30, for example, further includes a second bonding layer 34. The second bonding layer 34 is arranged between the first metal layer 15 and the second metal layer 35 in the thickness direction of the second bonding layer 34. The second bonding layer 34, for example, includes at least one selected from Cu and Ag. The second bonding layer 34 may include elements such as Mg, Sn, Ti, and Al. For example, the content of each element of Mg, Sn, Ti, and Al in the second bonding layer 34 is 1% by mass or less.

[0088] like Figure 3 As shown, for example, the thermoelectric conversion layer 11 is disposed in the thickness direction between the first composite metal layer 32 and the second composite metal layer 33. The first composite metal layer 32 and the second composite metal layer 33 include the first bonding layer 14, the first metal layer 15, the second bonding layer 34 and the second metal layer 35, respectively.

[0089] Thermoelectric conversion element 30 can be manufactured, for example, in the same manner as thermoelectric conversion element 10. The raw material of second bonding layer 34 is, for example, a paste composition containing a metal component. The raw material of second metal layer 35 is, for example, a metal plate.

[0090] Figure 42 is a cross-sectional view schematically showing another example of the thermoelectric conversion element of Embodiment 2. For example, when the second bonding layer 34 and the second metal layer 35 contain the same type of metal, the boundary between the second bonding layer 34 and the second metal layer 35 may not be clear in the cross section of the thermoelectric conversion element 30. For example, when the second bonding layer 34 and the second metal layer 35 both contain Cu or Ag, their boundary is not clear, and the second bonding layer 34 and the second metal layer 35 appear to be one layer. In this case, Figure 4 As shown, the portion that appears to be one layer can be regarded as the second metal layer 35 .

[0091] (Implementation 3)

[0092] Figure 5 1 is a perspective view showing an example of a thermoelectric conversion module of the present disclosure. Figure 5 As shown, the thermoelectric conversion module 100 includes a p-type thermoelectric converter 20, an n-type thermoelectric converter 10a, and a first electrode 51. The n-type thermoelectric converter 10a includes a thermoelectric conversion element 10 or a thermoelectric conversion element 30. The thermoelectric conversion material contained in the p-type thermoelectric converter 20 is not limited to a specific material, and for example, includes a known p-type thermoelectric conversion material. The first electrode 51 electrically connects one end of the p-type thermoelectric converter 20 to one end of the n-type thermoelectric converter 10a. According to such a configuration, even if the thermoelectric conversion module 100 is placed in a high-temperature air environment, it is easy to suppress the increase in resistance of the thermoelectric conversion element 10 or the thermoelectric conversion element 30 contained in the n-type thermoelectric converter 10a.

[0093] like Figure 5 As shown, the thermoelectric conversion module 100 further includes, for example, a second electrode 52 and a third electrode 53. The second electrode 52 is electrically connected to the other end of the p-type thermoelectric converter 20. The third electrode 53 is electrically connected to the other end of the n-type thermoelectric converter 10a.

[0094] The thermoelectric conversion module 100 further includes, for example, a pair of substrates 60. One of the pair of substrates 60 is arranged in contact with the first electrode 51, and the other of the pair of substrates 60 is arranged in contact with the second electrode 52 and the third electrode 53. According to such a configuration, in the thermoelectric conversion module 100, it is difficult to generate temperature deviation in a direction parallel to the main surface of the substrate 60. The material of the substrate 60 is not limited to a specific material. The substrate 60 includes, for example, aluminum oxide or aluminum nitride.

[0095] (Implementation 4)

[0096] Figure 6 is a side view showing a thermoelectric conversion system of Embodiment 4. Figure 6As shown, the thermoelectric conversion system 300 includes the thermoelectric conversion module 100 and the heat source 70. The heat source 70 is disposed on the first electrode 51 side of the thermoelectric conversion module 100.

[0097] According to the thermoelectric conversion system 300 , it is possible to generate electric power by generating a temperature difference in the thermoelectric conversion module 100 using the heat from the heat source 70 .

[0098] In the thermoelectric conversion system 300, the heat source 70 may include a heat transfer tube, into which a predetermined heat medium is introduced. The heat medium may be a gas such as exhaust gas, or a liquid such as water and oil. The heat source 70 may include a plate for collecting radiant heat.

[0099] like Figure 6 As shown, for example, in the thermoelectric conversion system 300 , one of the pair of substrates 60 of the thermoelectric conversion module 100 is arranged between the heat source 70 and the thermoelectric conversion module 100 .

[0100] (Note)

[0101] Based on the above records, the following technical solutions are disclosed.

[0102] (Technology 1)

[0103] A thermoelectric conversion element comprises a first metal layer and a thermoelectric conversion part, wherein the thermoelectric conversion part contains Mg and at least one selected from Sb and Bi, the thermoelectric conversion part comprises a thermoelectric conversion layer and a first bonding layer, the first bonding layer is arranged between the first metal layer and the thermoelectric conversion layer in the thickness direction of the thermoelectric conversion layer, the first bonding layer contains at least one selected from Fe and Ni, and the first bonding layer satisfies a first condition represented by 2.5≤α / β≤6.5, in which α is the content rate of Mg in the first bonding layer based on the number of atoms, and β is the sum of the content rates of Sb and Bi in the first bonding layer based on the number of atoms.

[0104] (Technique 2)

[0105] According to the thermoelectric conversion element described in the first technique, the first bonding layer includes particles containing at least one selected from Fe and Ni, and a phase existing between the particles and forming a solid phase different from the particles, and the phase contains Mg.

[0106] (Technique 3)

[0107] According to the thermoelectric conversion element described in technology 1 or 2, the first bonding layer satisfies the second condition represented by 0.002<α / γ<0.6, in which γ is the sum of the contents of Fe and Ni in the first bonding layer based on the number of atoms.

[0108] (Technique 4)

[0109] According to the thermoelectric conversion element described in any one of technologies 1 to 3, the sum γ of the contents of Fe and Ni based on the number of atoms in the first bonding layer satisfies the third condition of γ ≥ 65%.

[0110] (Technique 5)

[0111] In the thermoelectric conversion element according to any one of techniques 1 to 4, the first metal layer contains at least one selected from the group consisting of Fe, Ni, Cu, and Ag.

[0112] (Technique 6)

[0113] The thermoelectric conversion element according to any one of technologies 1 to 5 also has a second metal layer, the second metal layer contains at least one selected from Cu and Ag, and the first metal layer is arranged between the second metal layer and the thermoelectric conversion part in the thickness direction of the first metal layer, and contains at least one selected from Fe and Ni.

[0114] (Technique 7)

[0115] A bonding material contains Mg and at least one selected from Fe and Ni, and is capable of bonding a thermoelectric conversion material and a metal member.

[0116] (Technology 8)

[0117] A thermoelectric conversion module comprises a p-type thermoelectric converter, an n-type thermoelectric converter, and an electrode electrically connecting one end of the p-type thermoelectric converter and one end of the n-type thermoelectric converter, wherein the n-type thermoelectric converter comprises the thermoelectric conversion element described in any one of Techniques 1 to 7.

[0118] (Technique 9)

[0119] A thermoelectric conversion system comprises the thermoelectric conversion module according to the eighth aspect and a heat source arranged on the electrode side.

[0120] (Technology 10)

[0121] A method of generating electricity includes generating electricity by generating a temperature difference using heat from a heat source in a thermoelectric conversion module according to technique 8.

[0122] (Technology 11)

[0123] A method for manufacturing a thermoelectric conversion element comprises heating a metal plate, a powder and a bonding material in a state where the bonding material is arranged between the metal plate and the powder in the thickness direction of the metal plate, sintering the powder, and bonding the metal plate to the sintered body of the powder, wherein the bonding material contains Mg and at least one selected from Fe and Ni, and the powder contains Mg and at least one selected from Sb and Bi.

[0124] (Technology 12)

[0125] According to the production method described in the eleventh aspect, the bonding material contains particles containing at least one selected from Fe and Ni, and the average particle size p of the particles satisfies the fourth condition represented by 0.5 μm ≤ p ≤ 100 μm.

[0126] Example

[0127] Hereinafter, the present disclosure will be described in detail with reference to Examples. However, the thermoelectric conversion material of the present disclosure is not limited to the specific embodiments described below.

[0128] <Example 1>

[0129] The raw material powders were weighed in a glove box with an argon atmosphere, and 2.00 g of Mg powder, 4.70 g of Sb powder, 2.63 g of Bi powder, and 0.03 g of Te were measured. The weighed raw material powders were sealed in a super-hard steel container model 8001 manufactured by SPEX Sample Prep together with super-hard steel balls. Then, the raw material powders sealed in the container were mixed for 2 hours using a vibration mill device model 8000D manufactured by SPEX Sample Prep, and a powder of thermoelectric conversion material was produced based on a mechanochemical reaction. Thus, a powder having Mg 3.2 Sb 1.5 Bi 0.49 Te 0.01 Powder of thermoelectric conversion material having a composition of and a La2O3 type crystal structure.

[0130] Measure 90g of cycloalkane solvent into a beaker, stir with a stirrer, and gradually add a total of 10g of butyl rubber adhesive in small amounts to prepare a 10% by weight adhesive solution. Add 6.93g of stainless steel powder (SUS304 powder), 0.07g of Mg powder and 3.0g of adhesive solution to a polyethylene container. The ratio of the amount of stainless steel powder added to the amount of Mg powder added is 99.0 on a mass basis. According to the volume-based particle size distribution of the stainless steel powder obtained by laser diffraction particle size distribution measurement, the particle size of the stainless steel powder is in the range of 1 micron to 50 microns. In addition, the average particle size (median particle size d50) of the stainless steel powder is about 10 microns. The contents of the container are shaken for 6 minutes with a vibration mill device to mix and obtain a paste-like bonding material of Example 1.

[0131] The bonding material of Example 1 was applied to one main surface of a stainless steel circular plate having a diameter of 19.9 mm and a thickness of 0.2 mm to form a bonding material coating film having a thickness of 0.1 mm.

[0132] The stainless steel disc having the coating film of the bonding material formed thereon was placed on a hot plate heated to 120° C., and the bonding material was dried for 15 minutes. In this way, two stainless steel plates with bonding materials were obtained.

[0133] In a glove box of argon atmosphere, each component was filled in a carbon sintering mold having an inner diameter of 20 mm in the following order: Here, two stainless steel plates with a bonding material were arranged so that a coating of the bonding material was in contact with the powder of the thermoelectric conversion material.

[0134] Carbon punch with 20mm outer diameter

[0135] Carbon sheet with 20mm diameter

[0136] 1st stainless steel plate with bonding material

[0137] 5.0g of thermoelectric conversion material powder

[0138] Second stainless steel plate with bonding material

[0139] Carbon sheet with 20mm diameter

[0140] Carbon punch with 20mm outer diameter

[0141] The above-mentioned sintering mold filled with raw materials was placed inside the chamber of the SPS Syntex spark plasma sintering device SPS-515S, and the environment of the sintering mold was adjusted to an argon atmosphere. While applying a pressure of 50 MPa inside the sintering mold, the sintering mold was heated to 850°C to sinter the powder of the thermoelectric conversion material and to join the powder of the thermoelectric conversion material to the stainless steel plate.

[0142] Next, the sintering mold was cooled to room temperature by furnace cooling, and then the contents inside the sintering mold were taken out and ground with grinding paper to remove the carbon pieces from the contents, thereby obtaining a laminate of Example 1.

[0143] The laminated body of Example 1 was cut with a diamond cutter to obtain 3.4 mm×3.4 mm×3.5 mm rectangular parallelepiped thermoelectric conversion elements of Example 1. Twelve thermoelectric conversion elements were obtained.

[0144] (Measurement of resistance)

[0145] The resistance between a pair of stainless steel plates in the thermoelectric conversion element of Example 1 was measured using a current source model 6221 manufactured by Keithley and a voltmeter model 2182A manufactured by Keithley according to the 4-terminal method. As shown in Table 1, the average resistance of the three thermoelectric conversion elements is 6 mΩ. The thermoelectric conversion element of Example 1 was placed in a box-type electric furnace model F-1404-P of Tokyo Glass Machinery set at 400°C and placed in an air environment at 400°C for 4 days for heat treatment. Then, after the electric furnace was restored to room temperature, the thermoelectric conversion element was taken out, and the surface of the stainless steel plate was polished with grinding paper to remove the oxide film on the surface. Then, the resistance between a pair of stainless steel plates in the thermoelectric conversion element was measured according to the 4-terminal method. As a result, the average resistance of the three thermoelectric conversion elements after heat treatment was 6.2 mΩ.

[0146] (Cross-sectional observation of thermoelectric conversion element)

[0147] The side of the thermoelectric conversion element of Example 1 was ground with grinding paper. Then, ion milling was performed using an argon ion milling device model EM TIC 3X manufactured by Leica to expose the cross section of the thermoelectric conversion element and obtain a sample for cross-sectional observation. The sample was observed using a scanning electron microscope (SEM model SU8220) manufactured by Hitachi High-Technologies. Figure 7 This is a SEM image of a cross section of the junction of the thermoelectric conversion element of Example 1. Figure 7 In the embodiment, the layer represented by symbol "51" is a layer containing a thermoelectric conversion material. The layer represented by symbol "52" is a bonding layer from a bonding material. The layer represented by symbol "53" is a stainless steel plate. Figure 7As shown in FIG. 1 , a layer structure was confirmed in the junction of the thermoelectric conversion element of Example 1. Figure 7 As shown, in the bonding layer indicated by the symbol "52", a first portion which is a dark portion in the form of particles and a second portion which is a bright portion existing between the particles are confirmed. The thickness of this layer is about 30 μm. Figure 7 In the same field of view, composition analysis was performed by energy dispersive X-ray spectroscopy (EDX). As a result, in addition to Mg, Sb and Bi contained in the thermoelectric conversion material were detected in the second part of the bonding layer. In addition to Mg, Sb and Bi, Cr, which is believed to be derived from stainless steel, was detected in the layer containing the thermoelectric conversion material. In the first part of the bonding layer, Fe, Ni and Cr were detected.

[0148] (Quantitative Analysis)

[0149] Based on the above SEM-EDX results, the content of each element in the bonding layer was determined based on the number of atoms. The results are shown in Table 1. Considering the influence of the measurement site on the measurement results, the size of the SEM-EDX measurement field was adjusted so that the measurement results were the average results in the bonding layer.

[0150] <Examples 2 to 4 and Comparative Examples 1 to 3>

[0151] Thermoelectric conversion elements of Examples 2 to 4 and Comparative Examples 1 to 3 were prepared in the same manner as in Example 1 except that the mass ratio of the amount of stainless steel powder added to the amount of Mg powder added was changed as shown in Table 1. In Comparative Example 1, no Mg powder was added. For each of these thermoelectric conversion elements, resistance measurement, cross-sectional observation, and quantitative analysis were performed in the same manner as in Example 1. The results are shown in Table 1.

[0152] <Example 5>

[0153] The thermoelectric conversion element of Example 5 was prepared in the same manner as in Example 1 except for the following points. An oxygen-free copper plate was used instead of the stainless steel plate. In addition, the heating temperature of the sintering mold was adjusted to 680° C. For the thermoelectric conversion element of Example 5, the resistance measurement, cross-sectional observation and quantitative analysis were carried out in the same manner as in Example 1. The results are shown in Table 1.

[0154] <Example 6>

[0155] The thermoelectric conversion element of Example 6 was prepared in the same manner as in Example 1 except for the following points. Instead of the stainless steel powder used in the preparation of the bonding material of Example 1, another stainless steel powder having a particle size of 100 microns or less was used. The average particle size of the stainless steel powder was 60 to 80 microns. For the thermoelectric conversion element of Example 6, the resistance measurement, cross-section observation and quantitative analysis were carried out in the same manner as in Example 1. The results are shown in Table 1. Figure 8 This is a SEM image of a cross section of the junction of the thermoelectric conversion element of Example 6. Figure 8 The thickness of the layer indicated by symbol "52", ie, the bonding layer, is in the range of about 100 micrometers to 150 micrometers.

[0156] <Example 7>

[0157] The same method as in Example 1 was used to prepare a Figure 3 Thermoelectric conversion element of Example 7 of the structure shown. A paste-like bonding material containing Mg and Cu is applied to a circular plate of oxygen-free copper, and the bonding material is dried to obtain two copper plates with bonding materials. In a sintering mold, each component is filled in the following order. Here, two copper plates with bonding materials are arranged in such a way that the bonding material of the copper plates with bonding materials is in contact with the stainless steel plate.

[0158] Carbon punch with 20mm outer diameter

[0159] Carbon sheet with 20mm diameter

[0160] 1st copper plate with bonding material

[0161] 1st stainless steel plate with bonding material

[0162] 5.0g of thermoelectric conversion material powder

[0163] Second stainless steel plate with bonding material

[0164] 2nd copper plate with bonding material

[0165] Carbon sheet with 20mm diameter

[0166] Carbon punch with 20mm outer diameter

[0167] The thermoelectric conversion element of Example 7 was subjected to resistance measurement, cross-sectional observation, and quantitative analysis in the same manner as in Example 1. The results are shown in Table 1.

[0168] As shown in Table 1, from the comparison between the examples and the comparative examples, if the condition of 2.5≤α / β≤6.5 is satisfied in the bonding layer of the thermoelectric conversion element, it is easy to suppress the increase in the resistance of the thermoelectric conversion element in high-temperature air.

[0169]

[0170] Industrial Availability

[0171] The thermoelectric conversion element disclosed herein can be used for applications such as power generation and temperature regulation.

[0172] Description of Reference Numerals

[0173] 10, 30 Thermoelectric conversion element

[0174] 10a n-type thermoelectric converter

[0175] 11 Thermoelectric conversion layer

[0176] 11a Thermoelectric conversion unit

[0177] 14 First bonding layer

[0178] 14a Particles

[0179] Phase 14b

[0180] 15 First Metal Layer

[0181] 20 p-type thermoelectric converter

[0182] 35 Second metal layer

[0183] 51 first electrode

[0184] 70 Heat Source

[0185] 100 Thermoelectric conversion module

[0186] 300 Thermoelectric Conversion System

Claims

1. A thermoelectric conversion element comprising a first metal layer and a thermoelectric conversion unit, The thermoelectric conversion unit contains Mg and at least one selected from Sb and Bi, The thermoelectric conversion unit includes a thermoelectric conversion layer and a first bonding layer. The first bonding layer is arranged between the first metal layer and the thermoelectric conversion layer in the thickness direction of the thermoelectric conversion layer. The first bonding layer contains at least one selected from Fe and Ni, The first bonding layer satisfies a first condition represented by 2.5≤α / β≤6.5, In the first condition, α is the content rate of Mg in the first bonding layer based on the number of atoms, and β is the sum of the content rates of Sb and Bi in the first bonding layer based on the number of atoms.

2. The thermoelectric conversion element according to claim 1, The first bonding layer includes particles containing at least one selected from Fe and Ni, and a phase existing between the particles and forming a solid phase different from the particles. The phase contains Mg.

3. The thermoelectric conversion element according to claim 1, The first bonding layer satisfies a second condition represented by 0.002<α / γ<0.6, In the second condition, γ is the sum of the contents of Fe and Ni in the first joining layer based on the number of atoms.

4. The thermoelectric conversion element according to claim 1, The sum γ of the contents of Fe and Ni based on the number of atoms in the first bonding layer satisfies the third condition, ie, γ ≥ 65%.

5. The thermoelectric conversion element according to claim 1, The first metal layer contains at least one selected from Fe, Ni, Cu, and Ag.

6. The thermoelectric conversion element according to claim 1, further comprising a second metal layer, The second metal layer contains at least one selected from Cu and Ag, The first metal layer is disposed between the second metal layer and the thermoelectric conversion portion in a thickness direction of the first metal layer, and contains at least one selected from Fe and Ni.

7. A bonding material comprising Mg and at least one selected from Fe and Ni, The bonding material can bond the thermoelectric conversion material and the metal member.

8. A thermoelectric conversion module comprising a p-type thermoelectric converter, an n-type thermoelectric converter, and an electrode electrically connecting one end of the p-type thermoelectric converter and one end of the n-type thermoelectric converter, The n-type thermoelectric converter includes the thermoelectric converter element according to claim 1 . 9 . A thermoelectric conversion system comprising the thermoelectric conversion module according to claim 8 , and a heat source disposed on the electrode side. 10 . A method of generating electric power, comprising generating electric power by generating a temperature difference using heat from a heat source in the thermoelectric conversion module according to claim 8 .

11. A method for manufacturing a thermoelectric conversion element, comprising heating a metal plate, a powder, and a bonding material in a state where the bonding material is arranged between the metal plate and the powder in a thickness direction of the metal plate, sintering the powder, and bonding the metal plate to a sintered body of the powder, The bonding material contains Mg and at least one selected from Fe and Ni, The powder contains Mg and at least one selected from Sb and Bi.

12. The manufacturing method according to claim 11, The bonding material contains particles containing at least one selected from Fe and Ni, The average particle size p of the particles satisfies a fourth condition represented by 0.5 μm ≤ p ≤ 100 μm.

Citation Information

Patent Citations

  • Guide apparatus for switching door in garbage wagon

    JP1986027281B2

  • Thermoelectric conversion element, and thermoelectric module equipped with the same

    JP2009260173A